The Stability of Tissue Plasminogen Activator (t-PA) - Gaffney, P J; Templeman, J; Curtis, A D; Campbell, P J (Thrombosis and Haemostasis, 1983)
Since tissue-type plasminogen activator (t-PA) derived from tissue culture and recombinant DNA procedures has been proposed for use in thrombolytic therapy in man, it is essential that the t-PA molecule should display reasonable stability in a lyophilised state to facilitate its usefulness. In this study, four laboratories compared the potencies of three preparations of t-PA following storage at 4°, 20°, 37° and 45° C, using each t-PA stored at -20° C as a reference (100% activity) in each case. A pig heart extract of t-PA was the most stable, losing no activity when stored for 30 days at 37° C, while two melanoma cell tissue culture extracts varied in their storage behaviour. One was quite stable at 37° C (losing about 3% of its activity) while the other lost about 16%. Thus both the pig heart t-PA and one t-PA from melanoma cell culture proved suitable for the further development of reference standards for t-PA activity.
Keywords: Tissue plasminogen activator; Stability